Mathematical modelling of filtration processes in problems of evaluation of level and quality of groundwaters - Олійник, Андрій Петрович; Штаєр, Лідія Омелянівна; Клапоущак, Оксана Ігорівна (Eastern-European Journal of Enterprise Technologies, 2013)
The article concerns the mathematical models of filtration of groundwaters taking into account the environmental (flooding) and technological (extraction of shale gas) factors. The models of Darcy and Forchheimer were considered with appropriate boundary conditions; the numerical implementation of the models was carried out. It was determined that the pattern of the filtration under conditions that V>>V2, where V is a typical filtration rate and without this condition, is identical, according to its qualitative measures. The peculiarities of the filtration process for the areas with different configurations of fluid invaded zones through the area boundary were determined; the impact of these zones on the spatial nature of the flow in the studied area was assessed. The obtained results permit to assess the level of groundwaters, and the peculiarities of their distribution in terms of environmental characteristics of the flow in the presence of different geometrical configuration of leakage zones through the studied area. These results can be used to assess the impact of the environmental and technological factors on water quality and to prevent flood waters.